Regional social infrastructure from the perspective of an ageing society - Szostak, Ewa (Regionalna infrastruktura społeczna z punktu widzenia starzenia się społeczeństwa, 2018)
This article aims to assess the state of the economy by highlighting the regional aspect from the perspective of an ageing population as well as to analyse the adjustments of the economy structure at the level of Polish regions in the area of silver and white economy to the needs of an ageing society. The age of 65+ was analysed. The rate of change in different regions is different, but the ageing process of society can be noticed everywhere. The creation of a silver and white economy is necessary in the face of ongoing processes. Visible delays in these areas are disturbing. It is the responsibility of the authorities to set goals and methods of their achievement in the field of shaping, for example, labour market policy, social insurance and healthcare. Methods used: descriptive, comparative, statistical analysis, synthesis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 537, s. 103-118
Keywords: ageing; silver economy; white economy; region; voivodeship; starzenie się; srebrna gospodarka; biała gospodarka; województwo